Blonanserin treatment in patients with methamphetamine-induced psychosis comorbid with intellectual disabilities - Okazaki K (Neuropsychiatric Disease and Treatment, 2016)
Kosuke Okazaki, Manabu Makinodan, Kazuhiko Yamamuro, Tomoyo Takata, Toshifumi Kishimoto Department of Psychiatry, Nara Medical University School of Medicine, Kashihara, JapanObjective: Methamphetamine (MA) use has recently been associated with high levels of psychiatric hospitalization and serious social dysfunction. MA use causes frequent psychotic symptoms, which can be treated with antipsychotics. However, people with intellectual disabilities (ID) are vulnerable to adverse effects resulting from treatment with antipsychotic medications.Method: We report two cases of MA-induced psychosis (MAP) in patients with ID who were treated with the antipsychotic blonanserin.Results: In both the cases presented, symptoms of psychosis were improved by switching medications from other antipsychotic drugs to blonanserin. Despite the presence of ID in these patients, no significant adverse effects, such as sedation, were detected after treatment with blonanserin.Conclusion: Blonanserin may be an effective and well-tolerated pharmacotherapeutical treatment for patients with MAP comorbid with ID. However, further work is necessary to validate this claim.Keywords: methamphetamine, methamphetamine-induced psychosis, intellectual disabilities, blonanserin